Bone Healing: In Vivo Sequestration of Innate Small Molecules to Promote Bone Healing (Adv. Mater. 8/2020). Issue 8 (24th February 2020) - Zeng, Yuze; Shih, Yu‐Ru V.; Baht, Gurpreet S.; Varghese, Shyni
Abstract : In article number 1906022, Shyni Varghese and co‐workers describe the application of a designer biomaterial "bandage" at the site of a bone injury to sequester and localize innate pro‐healing signaling molecules that promote vascularization and healing. The biomaterial‐assisted sequestration of adenosine leverages the transient surge of extracellular adenosine following injury to prolong local adenosine signaling, offering a versatile solution to utilizing adenosine as a potential therapeutic for tissue repair.